The world of heroes in the archaic hexametric poetry - Werner, Christian (Romanitas - Revista de Estudos Grecolatinos, 2013)
A discussion regarding the world presented by the Homeric poems depends on discussion on the poems’ poetics and how they can be pinned down in a wider tradition, early Greek hexametric poetry. In this paper I tackle the issue of how this tradition handles the heroic world as both near to and far from the world of the audience.